The relationship of rewards to employee's performance in the e-banking environment among local banks in Kuala Lumpur - Sivakumar, P. Perumal (2017)
The purpose of this study is to examine the relationship between reward system (monetary and non-monetary rewards) and employee’s performances in the e-banking environments among local bank in Kuala Lumpur. A survey involving 150 banking staff which involved in the e-banking environments. Three monetary rewards factors (salary, merit paid and bonus) and five non-monetary rewards factors (recognition, learning opportunity, challenging work, career advancement and work autonomy) were tested. The data was analyzed using SPSS. Pearson Correlation Coefficient and Regression analysis was run to examine the effect of rewards on the employee performances in the e-banking environments. The result revealed that there is a positive significant relationship between rewards system (monetary and nonmonetary) and employee’s performances. The result of this of this study is able to assist an organisation to understand the sentiment of the employee’s views towards the rewards.